Research status and prospects of pituitary adenomas in conjunction with neurological and psychiatric disorders and the tumor microenvironment - Cui, Siyuan; Chen, Sainan; Wu, Xuechao; Wang, Qing (Frontiers in Neuroscience, 2024)
Patients with pituitary neuroendocrine tumors (PitNETs) often experience neuropsychiatric disorders due to factors such as hormonal imbalances, and inadequate management of medications, surgeries, and radiation therapies. Commonly observed disorders include depression, anxiety, and cognitive dysfunction, which significantly impact patients' quality of life and prognosis. PitNETs have a significant presence of immune cells within the TME, predominantly macrophages and T lymphocytes. These immune cells secrete a variety of cytokines, growth factors, and chemokines, which regulate the biological behaviors of PitNETs, including tumor initiation, proliferation, migration, invasion, and angiogenesis. In addition, this review provides a pioneering summary of the close relationships between the aberrant secretion of proinflammatory cytokines within the TME of PitNETs and the occurrence of neuropsychiatric disorders, along with their potential underlying mechanisms. The cytokines produced as a result of TME dysregulation may affect various aspects of the central nervous system, including neurotransmitter metabolism, neuroendocrine function, and neurovascular plasticity, thereby leading to a higher susceptibility to neurobehavioral disorders in PitNET patients.